SPIGELIAN HERNIA – A RARE HERNIA, A CASE IN A RARE SITE. - DR .PRAN GOPAL SARKAR. (International Journal of Pharma and Bio Sciences, 2013)
Spigelian hernia occurs through defects in transversus abdominis aponeurosis due to various etiology. Site is usually below arcuate line of Douglus- but rarely cited at higher level. Its incidence is 0.12 % of abdominal wall hernias. It is more rare to be detected at a higher locus above umbilicus. Although recently laparoscopic repair getting popularity, open repair still seems to be the commonest procedure done in this part of world. An obese patient with COPD presented with a reducible swelling at upper abdomen. Operatively it was a Spigelian hernia with big neck. Open pre-peritoneal mesh placement repair was done. patient recovered well. Open repair with mesh is proved to be well suitable in our case of spigelian hernia in a very uncommon above umbilicus site Spigelian hernia at the uncommon supra umbilical site is sparingly reported. This is such a case, with other comorbid conditions. It responded well with the classical open repair